Specific tolerance to neural allografts induced with an antibody to the interleukin 2 receptor. - Wood, M; Sloan, D; Dallman, M; Charlton, H (1993)
Despite considerable evidence documenting the central nervous system as a site of immunological privilege, immune responses do occur within the brain and neural allografts between major histocompatibility complexes (MHC) and minor antigen incompatible rat strains may be rejected. The survival of completely MHC incompatible neural allografts has been found to be prolonged indefinitely after administration of a monoclonal antibody (mAb) to the interleukin 2 receptor (IL-2R) for 10 d after transplantation. Here we present evidence that rats with long-term surviving lateral ventricular neural allografts, after anti-IL-2R treatment, accept subsequent neural allografts from the same donor strain, placed in a peripheral nonprivileged site, but rapidly reject third-party grafts. Thus, treatment with a mAb to the p55 chain of the IL-2R has resulted in the specific acceptance of second grafts of fully allogeneic neural tissue. These results suggest that ongoing interaction between elements of the host immune system and alloantigen within the brain maintains the tolerant state and furthermore, that interruption of signaling through the IL-2R may be important in allospecific tolerance induction.